2021
DOI: 10.1055/s-0041-1723070
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Secondary Alveolar Bone Graft on Canine Eruption: Systematic Review

Abstract: There are controversies related to the effects of bone grafts on tooth eruption and impaction in patients with cleft lip and palate. The aim of this systematic review was to evaluate the effectiveness of bone grafting on eruption of canines in patients with unilateral cleft lip and palate (UCLP). An electronic search was conducted in six electronic databases and gray literature, without limitations on year of publication or language. The primary outcome was the increase in rate of canine eruption; the secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Its biological effect has the potential to inflammatory control and repair of gingival tissues in different clinical conditions. 46 47 Clinical experiments with humans could check the efficacy of what appears to be a highly promising method for obtaining an antibacterial GIC.…”
Section: Discussionmentioning
confidence: 99%
“…Its biological effect has the potential to inflammatory control and repair of gingival tissues in different clinical conditions. 46 47 Clinical experiments with humans could check the efficacy of what appears to be a highly promising method for obtaining an antibacterial GIC.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have instead found a positive relationship between agenesis of the lateral incisor and canine impaction, confirming the effect of the lateral incisor in guiding the canine to the normal eruption path (Enemark et al, 2001; Simões Holz et al, 2018). A recent systematic review found that there is very low certainty of evidence confirming the association between the agenesis of the lateral incisors and the impaction of the canines (Lacerda-Santos et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They didn’t find any association between congenital absence of lateral incisors and canine root completion, canine eruption failure. Meanwhile, some studies found an association between increase in the rate of canine impaction and agenesis of lateral incisor, with very low certainty of evidence 12 . Some studies mentioned insufficient arch space of CLP patients is proposed to be associated with canine impactions 13 others mentioned there is no relationship between canine impaction and dental crowding 14 .…”
Section: Introductionmentioning
confidence: 99%